Study on the Stribeck Curve of Slider Bearing Lubrication State under Different Load - Fang Qunling; Sun Huer; Liu Weixiong (Jixie chuandong)
In order to study the change law for Stribeck curve of the sliding bearings under different loads,the pin disc friction test rig is established,the thickness of oil film and friction coefficient are collected by changing the load and speed. The curve of friction coefficient and pressure,speed,viscosity,namely Stribeck curve are plotted by using the MATLAB. The experimental results show that,with the increase of the speed,the friction coefficient decreased at first and then increased. The smaller the load,the sooner enter into the bottom of Stribeck curve,the easier to achieve fluid lubrication,the bearing lubrication state can be improved effectively by changing the load of bearing.